PDE5 Inhibition Ameliorates Visceral Adiposity Targeting the miR-22/SIRT1 Pathway: Evidence From the CECSID Trial - Fiore, Daniela; Gianfrilli, Daniele; Giannetta, Elisa; Galea, Nicola; Panio, Giuseppe; di Dato, Carla; Pofi, Riccardo; Pozza, Carlotta; Sbardella, Emilia; Carbone, Iacopo; Naro, Fabio; Lenzi, Andrea; et al. (The journal of clinical endocrinology and metabolism, 2016)
Context:Visceral adiposity plays a significant role in cardiovascular risk. PDE5 inhibitors (PDE5i) can improve cardiac function and insulin sensitivity in type 2 diabetes patients.Objective:To investigate whether PDE5i affect visceral adipose tissue (VAT), specifically epicardial fat (epicardial adipose tissue [EAT]), and what mechanism is involved, using microarray-based profiling of pharmacologically modulated microRNA (miRNAs).Design:Randomized, double-blind, placebo-controlled study in type 2 diabetes.Patients and Intervention:A total of 59 diabetic patients were randomized to receive 100-mg/d sildenafil or placebo for 12 weeks. Fat biopsies were collected in a subgroup of patients. In a parallel protocol, db/db mice were randomized to 12 weeks of sildenafil or vehicle, and VAT was collected.Main Outcomes and Measures:Anthropometric and metabolic parameters, EAT quantification through cardiac magnetic resonance imaging, array of 2005 circulating miRNAs, quantitative PCR, and flow cytometry of VAT.Results:Compared with placebo, sildenafil reduced waist circumference (P = .024) and EAT (P = .045). Microarray analysis identified some miRNAs differentially regulated by sildenafil, including down-regulation of miR-22-3p, confirmed by real-time quantitative PCR (P < .001). Sildenafil's modulation of miR-22-3p expression was confirmed in vitro in HL1 cardiomyocytes. Up-regulation of SIRT1, a known target of miR-22-3p, was found in both serum and sc fat in sildenafil-treated subjects. Compared with vehicle, 12-week sildenafil treatment down-regulated miR-22-3p and up-regulated Sirtuin1 (SIRT1) gene expression in VAT from db/db mice, shifting adipose tissue cell composition toward a less inflamed profile.Conclusions:Treatment with PDE5i in humans and murine models of diabetes improves VAT, targeting SIRT1 through a modulation of miR-22-3p expression.